The Value of Legislative Versus Electoral Experience and Gender in Explaining Candidate List Placement in Closed-List PR. Issue 2 (4th March 2017) - Chiru, Mihail; Popescu, Marina
Abstract : Candidates' political qualities and personal characteristics reflect what priorities political parties have when they nominate for viable seats. The limited research on the link between candidate characteristics and ranking on closed lists is an important hiatus in understanding legislative recruitment since in closed list PR nomination to top positions on viable lists virtually guarantees election. We address the issue by analyzing longitudinally the determinants of candidate list placement in Romania, an intriguing case given its low proportion of reelected incumbents and women MPs. Our findings indicate that while male candidates are placed higher up on the lists than women, the positive effect of incumbency is larger for female than male incumbents.